2015
DOI: 10.1134/s0016793215010119
|View full text |Cite
|
Sign up to set email alerts
|

Possible influence of telluric current on seismicity of the Earth’s crust in seismoactive zones

Abstract: A physical model is proposed for the possible effect of telluric currents on macrofracturing in the Earth's crust and the triggering of earthquakes via the interaction of telluric currents with the geomagnetic field. For implementation of the considered processes, a an escalated regime due to positive feedback between the decrease in electrical conductivity of the developing earthquake source and the increases in current and pressure in this source was established. Estimates of characteristic earthquake trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We use internal interaction as the modern geodynamic process manifestation concept as the main one for the Altai-Sayan mountainous region, Junggar Basin, and Tien Shan [13][14][15]. This greatly corresponds with the ideas from [16][17][18][19][20][21]. This theoretical model helps us to estimate interrelationship between some observed electromagnetic phenomena and earthquake development processes in seismoactive zones [22][23].…”
Section: Introductionmentioning
confidence: 96%
“…We use internal interaction as the modern geodynamic process manifestation concept as the main one for the Altai-Sayan mountainous region, Junggar Basin, and Tien Shan [13][14][15]. This greatly corresponds with the ideas from [16][17][18][19][20][21]. This theoretical model helps us to estimate interrelationship between some observed electromagnetic phenomena and earthquake development processes in seismoactive zones [22][23].…”
Section: Introductionmentioning
confidence: 96%
“…There are several publications, few so far, which are concerned with the influence of the Sun's electromagnetic radiation and magnetic storms on seismicity (Barsukov, 1991;Sobolev et al, 2001;Yesugey, 2009;Jeffrey and Jeremy, 2013;Trenkin, 2015). Zakrzhevskaya and Sobolev (2004) demonstrated that the rate of earthquakes with magnitudes equal to or greater than 3 increased during 2-7 days after storms in some regions of Central Asia, the Caucasus, and America.…”
Section: Introductionmentioning
confidence: 99%
“…An idea was discussed on a possible generation of additional stresses in the Earth crust due to the magnetic field variation [Duma and Ruzhin, 2003;Tren'kin, 2015]. In this paper we make an attempt to validate a possibility of earthquake triggering by solar flare based on electromagnetic triggering phenomena recently discovered in the field [Tarasov et al, 1999[Tarasov et al, , 2000Tarasov and Tarasova, 2004;Chelidze et al, 2006] and laboratory [Bogomolov et al, 2004;Avagimov et al, 2006;Lapshin et al, 2016;Chelidze et al, 2002;Novikov et al, 2017] experiments.…”
Section: Introductionmentioning
confidence: 99%